Robust Control of Electric Vehicle Powertrain Torsional Vibration based on μ-method - Duan Xiaoya; Yu Peng; Zhang Tong; Sun Ling (Jixie chuandong)
In view of the torsional vibration of an electric vehicle（EV） driveline,based on the blendingμ integrated robust control theory,the control method of driveline is studied.Firstly,the driveline uncertainty model of a central-driven pure EV is established,considering the high-order unmodeled uncertainty of permanent magnet synchronous motor and the parameter perturbation.Then,μ-method is adopted to design the driveline robust controller.Finally,in order to verify the validity of the designed controller,the simulation and calculation are conducted by using Matlab / Simulink.Results show that the control strategy can enhance the robust performance and robust stability of the system,and reduce the possibility of system instability effectively.